2014
DOI: 10.1002/ajmg.a.36730
|View full text |Cite
|
Sign up to set email alerts
|

A 12q24.31 interstitial deletion in an adult male with MODY3: Neuropsychiatric and neuropsychological characteristics

Abstract: A 39-year-old male patient with a disharmonic intelligence profile and juvenile diabetes mellitus is described. At 14 months of age, minor facial dysmorphisms were noticed. He had delayed motor development, obesity at early age, and a diagnosis of insulin-dependent diabetes at the age of 10 years. He successfully completed secondary education and has been engaged in unskilled work activities, living independently. Upon examination, no psychiatric symptoms were present and his neuropsychological profile showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…And HNF1A, POU2F1 significantly regulated blue and yellow , blue and darkred , respectively. It has been showed that HNF1A is associated with neuropsychiatric and neuropsychological characteristics 26 , 27 . The alternative promoter usage and differential expression of POU2F1 transcript variants has an impact on cerebellar development 28 , lens and olfactory placode development 29 .…”
Section: Resultsmentioning
confidence: 99%
“…And HNF1A, POU2F1 significantly regulated blue and yellow , blue and darkred , respectively. It has been showed that HNF1A is associated with neuropsychiatric and neuropsychological characteristics 26 , 27 . The alternative promoter usage and differential expression of POU2F1 transcript variants has an impact on cerebellar development 28 , lens and olfactory placode development 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The condition may also be associated with hepatic adenomatosis, bile acid synthesis alteration, decreased pancreatic volume, pancreatic dysfunction and other diseases [37,38,[55][56][57][58]. The patients also have elevated urinary glucose due to low renal threshold for glucose in this genetic subtype [59].…”
Section: Modymentioning
confidence: 99%